(untitled) (Research, Society and Development, 2020)
The objective was to describe the action on hand hygiene, carried out in rooming-in at a university hospital in Northeastern Brazil, using light technology, since there is great potential for this type of technology to add bond and adherence to what is reported. In addition, the involvement of the entire team in this process is essential, such as nursing students, for example, since this profession has an educating and promoting care character. In order to take actions on this subject, this study is an experience report, with qualitative and descriptive-exploratory research, so that objects such as eye sales, gouache paint and a parody with a view to raising awareness among professionals. In fact, it became necessary to develop an initiative to raise awareness among professionals about hand hygiene, using health education. Therefore, it is evident that the experience of an intervention based on light technologies provided an opportunity to associate theory with practice, and it is clear that actions of this type must be addressed frequently. Because, it brings benefits, such as the possible increase in hand hygiene adherence through the improvement of structural conditions in the sector, which allow the professional to carry out preventive measures of infections at favorable times.